Research of price movements of common stocks of Sberbank of Russia from position of the technical analysis - S. I. Tarakanov (Путеводитель предпринимателя, 2020)
In the article the price movements of common stocks of Sberbank of Russia from the middle of 2017 from position of the technical analysis is investigated. The movements of stocks are compared to the movement of the index of MICEX. Their similarity is noted. The best description among indicators is shown by simple moving averages.